Peer Victimization and Dating Violence Among LGBTQ Youth: the Impact of School Violence and Crime on Mental Health Outcomes - Espelage, Dorothy L. (Youth violence and juvenile justice, 2018)
This study examined the moderating role of school violence and peer victimization on the association between sexual orientation and mental health. The sample consisted of 11,794 high school students (Mage = 16, SD = 1.23; female assigned at birth = 51%; 1.8% identified as transgender) across 23 schools. Participants completed a self-report survey that assessed sexual orientation, ethnicity, gender identity, victimization experiences (e.g., peer and dating), perceptions of school violence and crime, as well as anxiety and suicidality. Multilevel analyses indicated that lesbian, gay, bisexual, questioning, and transgender (LGBTQ) individuals with lower rates of victimization had significantly lower rates of suicidality compared to LGBTQ individuals with higher rates of victimization. LGBTQ individuals in schools with high student perceptions of school violence and crime had higher suicidality than their non-LGBTQ counterparts. LGBTQ youth in schools with lower school violence and crime levels had lower rates of suicidality than their non-LGBTQ counterparts. Interventions need to consider multiple forms of victimization and school environment as potential risk and protective factors for LGBTQ youth.